1979
DOI: 10.1037/0022-3514.37.6.1017
|View full text |Cite
|
Sign up to set email alerts
|

Psychological androgyny: A case of mistaken identity?

Abstract: This article critically discusses theoretical and methodological issues raised by psychological androgyny research and theory. A number of problematic assumptions shared by this approach and the previous masculinity/femininity approach are detailed. The first part of the article considers whether inventories devised to tap general sex stereotypes should be used as individual personality measures. Alternative forms of cognitive structures, linking sex, other person features, and behavioral rules, are described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(87 citation statements)
references
References 53 publications
4
81
0
2
Order By: Relevance
“…Dans la mesure où ces rôles sont prédéterminés par la société et où il existe une cloison étanche entre masculinité et féminité, le rôle du genre sera étroitement relié à l'identité du genre. De fait, les perturbations psychologiques sont souvent associées au manque d'harmonie entre ces deux composantes (Lynn, 1959;Locksley et Colten, 1979). Money (1973) postule l'isomorphisme de ces deux dimensions, puisqu'il écrit que «le rôle du genre représente l'expression publique de l'identité du genre, et (que) l'identité du genre est l'expérience intime du rôle du genre.» La différence entre ces deux élé-ments serait que «le rôle du genre relève du comportement et de l'observation empirique, alors que l'identité du genre relève de l'esprit ou de la pensée, et d'opérations inférentielles».…”
Section: La Terminologieunclassified
“…Dans la mesure où ces rôles sont prédéterminés par la société et où il existe une cloison étanche entre masculinité et féminité, le rôle du genre sera étroitement relié à l'identité du genre. De fait, les perturbations psychologiques sont souvent associées au manque d'harmonie entre ces deux composantes (Lynn, 1959;Locksley et Colten, 1979). Money (1973) postule l'isomorphisme de ces deux dimensions, puisqu'il écrit que «le rôle du genre représente l'expression publique de l'identité du genre, et (que) l'identité du genre est l'expérience intime du rôle du genre.» La différence entre ces deux élé-ments serait que «le rôle du genre relève du comportement et de l'observation empirique, alors que l'identité du genre relève de l'esprit ou de la pensée, et d'opérations inférentielles».…”
Section: La Terminologieunclassified
“…Unlike others before them who have also noted the masculine advantage but who have attributed it to artifact (Locksley & Colten, 1979;Silvern & Ryan, 1979), Taylor and Hall viewed the M and F scales of the BSRI and the PAQ as valid indices of masculinity and femininity. They suggested that masculinity is in fact healthier in our society than femininity, and that this is a societal problem which should be addressed.…”
Section: Masculinity Versus Androgyny As a Predictor Of Psychologicalmentioning
confidence: 99%
“…Theoretical Critiques of the BSRI and the PAQ A cogent theoretical critique of both the BSRI and the PAQ has been presented by Locksley and Colten (1979). They noted the rapid acceptance of the above measures and suggested that androgyny theory has not been subjected to the usual rigorous scientific scrutiny because of its political implications.…”
Section: A Brief History Of Androgyny Researchmentioning
confidence: 99%
See 2 more Smart Citations